Pengaruh Love of Money dan Sifat Machiavellian terhadap Kecenderungan Fraud Accounting dengan Gender sebagai Variabel Moderasi - Annisa Erma Ayunda; Nayang Helmayunita (Jurnal Eksplorasi Akuntansi, 2022)
This study aims to analyze the effect of love of money and machiavellian on the tendency of accounting fraud with gender as a moderating variable. This research is an associative causality study with a quantitative approach. The population in this study were undergraduate students of Accounting, Faculty of Economics, Padang State University and Andalas University. The number of sample members was determined through the slovin formula so that 166 respondents were obtained. The sample in this study was S1 Accounting students entering 2018 at Padang State University and Andalas University with the condition that they had passed business ethics courses and the accounting profession and auditing courses. The data collection method used a questionnaire distributed via google form. The data used in this study is primary data. The hypothesis in this study was tested using moderated regression analysis (MRA). The results show that love of money has no effect on the tendency of accounting fraud, Machiavellian has a positive effect on the tendency of fraud accounting, and gender is not able to moderate love of money and Machiavellian on the tendency of fraud accounting.